Teucrium × pierae nothosp. nov. (sect. Polium, Lamiaceae), nuevo híbrido para la flora peninsular ibérica. Teucrium × pierae nothosp. nova (sect. Polium, Lamiaceae), a new hybrid for the Iberian Peninsula - Gómez, José; Ferrer-Gallego, P. Pablo; Roselló, Roberto; Guillén, Alberto; Laguna, Emilio; Peris, uan B. (Acta Botanica Malacitana, 2013)
Teucrium × pierae nothosp. nova (sect. Polium, Lamiaceae), a new hybrid for the Iberian Peninsula Palabras clave. Albacete, España, híbrido, Lamiaceae, Teucrium × pierae. Key words. Albacete province, hybrid, Lamiaceae, Spain, Teucrium × pierae.